2013
DOI: 10.1523/jneurosci.2307-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Multistate Structural Modeling and Voltage-Clamp Analysis of Epilepsy/Autism Mutation Kv10.2–R327H Demonstrate the Role of This Residue in Stabilizing the Channel Closed State

Abstract: Voltage-gated potassium channel Kv10.2 (KCNH5) is expressed in the nervous system, but its functions and involvement in human disease are poorly understood. We studied a human Kv10.2 channel mutation (R327H) recently identified in a child with epileptic encephalopathy and autistic features. Using multistate structural modeling, we demonstrate that the Arg327 residue in the S4 helix of voltage-sensing domain has strong ionic interactions with negatively charged residues within the S1-S3 helices in the resting (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 45 publications
3
41
0
3
Order By: Relevance
“…We have previously studied a voltagegated potassium channel mutation (K v 10.2-R327H) associated with epilepsy/ autism (Yang et al, 2013b). R327 is one of the critical positively charged residues (R2) within the S4 helix of the K v 10.2 channel.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously studied a voltagegated potassium channel mutation (K v 10.2-R327H) associated with epilepsy/ autism (Yang et al, 2013b). R327 is one of the critical positively charged residues (R2) within the S4 helix of the K v 10.2 channel.…”
Section: Discussionmentioning
confidence: 99%
“…Using multistate modeling, we showed that R327 has strong ionic interaction with negatively charged residues of the S1-S3 helices in the closed but not open state of the channel. The R327H K v 10.2 mutation weakens these interactions, thus making it easier to open the channel (Yang et al, 2013b).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations